2016
DOI: 10.1158/0008-5472.can-16-0268
|View full text |Cite|
|
Sign up to set email alerts
|

Chromatin Remodeling Factor LSH Drives Cancer Progression by Suppressing the Activity of Fumarate Hydratase

Abstract: Chromatin modification is pivotal to the epithelial-mesenchymal transition (EMT), which confers potent metastatic potential to cancer cells. Here, we report a role for the chromatin remodeling factor lymphoid-specific helicase (LSH) in nasopharyngeal carcinoma (NPC), a prevalent cancer in China. LSH expression was increased in NPC, where it was controlled by the Epstein-Barr virus-encoded protein LMP1. In NPC cells in vitro and in vivo, LSH promoted cancer progression in part by regulating expression of fumara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 56 publications
4
100
0
Order By: Relevance
“…Although it has been extensively reported that FH deficiency is associated to fumarate-dependent epigenetic deregulation, supporting the notion of FH as a tumor suppressor, the molecular mechanisms by which FH gene expression is controlled is not well clarified. It has been recently reported that in nasopharyngeal carcinoma, the chromatin remodeling factor lymphoid-specific helicase binds the FH promoter and recruits the epigenetic silencer factor G9a to inhibit the transcription of FH (213). The FH reduction promoted an unbalance in the TCA intermediates, with a decrease in malate levels and a concomitant increase in αKG amount.…”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been extensively reported that FH deficiency is associated to fumarate-dependent epigenetic deregulation, supporting the notion of FH as a tumor suppressor, the molecular mechanisms by which FH gene expression is controlled is not well clarified. It has been recently reported that in nasopharyngeal carcinoma, the chromatin remodeling factor lymphoid-specific helicase binds the FH promoter and recruits the epigenetic silencer factor G9a to inhibit the transcription of FH (213). The FH reduction promoted an unbalance in the TCA intermediates, with a decrease in malate levels and a concomitant increase in αKG amount.…”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 99%
“…The FH reduction promoted an unbalance in the TCA intermediates, with a decrease in malate levels and a concomitant increase in αKG amount. Deregulation of TCA metabolites in nasopharyngeal carcinoma cells induces the recruitment of IKKα to the promoter regions of genes involved in the EMT program, causing the downregulation of E-cadherin and ZO-1 and the parallel upregulation of the mesenchymal marker vimentin, leading to EMT, migration and invasion in vitro , and increase metastasis in vivo (213). …”
Section: Metabolic Pathways That Controls Emtmentioning
confidence: 99%
“…Interestingly, LSH-mediated CG methylation can modulate gene activity and influence neuron lineage commitment 21. Reports show that LSH contributes to the malignant progression of prostate cancer, melanoma, and nasopharyngeal carcinoma 20, 22, 23. However, the clinical significance of LSH in gliomas and which mechanism involved in the regulation of LSH remain poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown that lymphoid-specific helicase (LSH), a SNF2-SWI chromatin remodeler, plays an essential role in cancer progression via regulation of fumarate hydratase (FH) [35]. Mechanistically, together with histone methyltransferase G9a, LSH is critical for the normal development of mammals and is involved in the establishment and maintenance of DNA methylation [36].…”
Section: The Regulation Of Raf-mek-mapk Involving Interactions Betweementioning
confidence: 99%
“…RASSF1A, the founding member of the RASSF family and RASSF5/NORE inhibits tumor growth and proliferation by targeting to signaling molecules of the MAPK family [23,35]. Phosphorylated ERK (pERK) is a key downstream component of the Ras/Raf/MEK/ERK signaling pathway.…”
Section: The Regulation Of Raf-mek-mapk Involving Interactions Betweementioning
confidence: 99%